Her Şey Bir Merhaba ile Başlar - Okur, Jeannette (Open textbook library., 2021)
Her Şey Bir Merhaba ile Başlar was developed for intermediate level Turkish language courses at the University of Texas at Austin. Intermediate learners and their instructors may use it for different purposes: self-study, classroom instruction, tutoring, or as a pastime. The lessons in Her Şey Bir Merhaba ile Başlar integrate reading, listening and viewing comprehension, writing and speaking practice, grammar, vocabulary, and cultural activities. Dozens of audio and video clips of Turkish speakers describing their lives, their culture, and their country support and enhance these activities. The Her Şey Bir Merhaba ile Başlar textbook, interactive H5P exercises, and YouTube channel comprise a media-rich open educational resource (OER) developed by Dr. Jeannette Okur at the University of Texas at Austin and published by the Center for Open Educational Resources and Language Learning under the U.S. Department of Education Title VI Grant #P229A180003, with additional support from the UT Liberal Arts Instructional Technology Services and the UT Center for Middle Eastern Studies.